2002
DOI: 10.1177/107554700202300306
|View full text |Cite
|
Sign up to set email alerts
|

Advancing Science Communication

Abstract: Scholars of science communication have identified many issues that may help to explain why science communication is not as “effective” as it could be. This article presents results from an exploratory study that consisted of an open-ended survey of science writers, editors, and science communication researchers. Results suggest that practitioners share many issues of concern to scholars. Implications are that a clear agenda for science communication research now exists and that empirical research is needed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
51
0
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(54 citation statements)
references
References 12 publications
0
51
0
3
Order By: Relevance
“…In addition, one fifth of the scientists in this survey agreed that scientists who engage with the public are less well regarded by other scientists. The increasing specialisation and technical complexity of science (Boulter , 1999), the vast growth in the volume of scientific knowledge (Shortland & Gregory, 1991), and the culture of distrust of journalists and broadcast media (Triese & Weigold, 2002) are other significant barriers to civic science. To overcome these barriers and increase scientists involvement in science communication it has been suggested that a change in the culture of science is required whereby public engagement becomes an integral part of the scientific process itself, supported by formal acknowledgement of the importance of these activities and the provision of training (Wellcome Trust/MORI, 2000).…”
mentioning
confidence: 99%
“…In addition, one fifth of the scientists in this survey agreed that scientists who engage with the public are less well regarded by other scientists. The increasing specialisation and technical complexity of science (Boulter , 1999), the vast growth in the volume of scientific knowledge (Shortland & Gregory, 1991), and the culture of distrust of journalists and broadcast media (Triese & Weigold, 2002) are other significant barriers to civic science. To overcome these barriers and increase scientists involvement in science communication it has been suggested that a change in the culture of science is required whereby public engagement becomes an integral part of the scientific process itself, supported by formal acknowledgement of the importance of these activities and the provision of training (Wellcome Trust/MORI, 2000).…”
mentioning
confidence: 99%
“…Given that most scientists lack formal training in science communication, it is not surprising to observe a variety of efforts and outcomes (Treise and Weigold 2002). For that reason, many members of the scientific community actively seek input, ideas, and inspiration on science communication from specialists (e.g., a public relations or communications office at their institution), non-scientific institutions (e.g., businesses), and colleagues who are known for successful communication experiences or initiatives.…”
mentioning
confidence: 99%
“…The "misty mirror" of science [Bucchi and Mazzolini, 2003], a reductive simplification of the scientific method [Weilgod, 2001], or the promotion of sensationalist pseudoscience [Gorney, 1992] are a few instances of the criticism addressed to scientific journalism. Such criticism is in contrast with the acknowledgement of the relationship of mutual dependence science and journalism have [Hartz and Chappell, 1997], and the role of the media as the main source of scientific information for citizens [Lieverouw, 1990;Nelkin, 1996;Treise and Weigold, 2002;Burns, O'Connor and Stocklmayer, 2003;Shäfer, 2010].…”
Section: Introductionmentioning
confidence: 86%
“…For more than a century science journalists have acted as mediators between science and the general public, thus taking on the task of conveying the progress of research and contributing, with their educational role, to shaping the critical opinion on scientific and technological development [Treise and Weigold, 2002]. Hence, it is possible to say that they have been the main creators of the social image of scientific research that has been projected.…”
Section: Introductionmentioning
confidence: 99%